Thermodynamic study on vapour-liquid equilibrium of toluene and several types of oil as absorbent - H Hendriyana; S Suhartono; Herri Susanto (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2011)
Thermodynamic study on vapour-liquid equilibrium of toluene and several types of oil as absorbent Gas cleaning system is one of important step in the utilization of biomass via gasification process. The producer gas obtained from the gasification process must be very clean before it is used in an internal combustion engine. In order to gaseous fuel get cleaned with a tar content below 100 mg/Nm3, a gas cleaning system using scrubbing oil is being developed and taking the advantage of a lower vapour pressure of oil than scrubbing water. Study on vapour-liquid equilibrium is being conducted to understand the phenomena taking place in the absorption of tar with oil. In our present study, the producer gas containing tar is represented using air containing toluene. This producer gas model with a toluene or benzene concentration then bubbled with a rate of 27.6 mL/min into a bath of oil at a various temperature. The progress of absorption of tar model in oil measured gas chromatography until saturated condition. Considering that the concentration of toluene in the gas stream is very low, the toluene and oil vapour-liquid equilibrium follows the Henry’s law. Prediction of Henry’s constants is also carried out using UNIFAC-FV model which is known to be suitable for hydrocarbon gases and high-boiling point hydrocarbon solvent. Keywords: tar, oil, Henry’s constant AbstrakSistem pembersihan gas merupakan salah satu langkah penting dalam pemanfaatan biomassa melalui proses gasifikasi. Gas produser yang dihasilkan dari proses gasifikasi harus sangat bersih sebelum digunakan dalam mesin pembakaran internal. Untuk mendapatkan bahan bakar gas yang bersih dengan kandungan tar di bawah 100 mg/Nm3. Sebuah sistem pembersihan gas dengan menggunakan minyak sebagai media penyerap dikembangkan dengan mengambil keuntungan dari tekanan uap minyak lebih rendah air penyerap. Studi kesetimbangan uap-cair yang dilakukan untuk memahami fenomena yang terjadi dalam penyerapan tar dengan minyak. Dalam kami studi ini, gas produser yang mengandung direpresentasikan dengan udara yang mengandung toluena. Model gas produser ini dibuat dengan menggelembungkan konsentrasi benzena atau toluena dengan laju 27,6 mL/menit ke dalam bak minyak pada berbagai suhu. Kemajuan penyerapan model tar dalam minyak diukur dengan cromathograpy gas sampai dengan kondisi jenuh. Mengingat konsentrasi toluena dalam aliran gas sangat rendah, maka kesetimbangan uap-cair toluena dan minyak mengikuti hukum Henry. Konstanta Henry juga dapat diprediksi dengan menggunakan model UNIFAC-FV yang cocok untuk gas hidrokarbon dan pelarut hidrokarbon dengan titik didih tinggi. Kata kunci: tar, minyak, konstanta Henry